2017
DOI: 10.1097/qai.0000000000001421
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Impact of Early Antiretroviral Therapy on the Performance of HIV Rapid Tests and HIV Incidence Assays

Abstract: BACKGROUND Antiretroviral therapy (ART) can down-regulate antibody responses to HIV infection. We evaluated the impact of early vs. delayed ART on the performance of HIV diagnostic and incidence assays. METHODS Samples were obtained from 207 participants in the HPTN 052 trial who were stably suppressed on ART for ≥4 years (Malawi sites; pre-ART CD4 cell count 350–550 cells/mm3 [early ART arm, N=180] or <250 cells/mm3 or an AIDS-defining illness [delayed ART arm, N=27]). Samples were tested with two HIV rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…A decrease in Ab detection after early treatment was also observed in other studies, which showed increased frequencies of false-negative results, weakly reactive HIV rapid test results, and increased numbers of indeterminate HIV-1 WB assay results (11,36). Of note, S/CO values of less than 10 by the ARC and BPX assays have frequently been associated with false-positive results (31,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A decrease in Ab detection after early treatment was also observed in other studies, which showed increased frequencies of false-negative results, weakly reactive HIV rapid test results, and increased numbers of indeterminate HIV-1 WB assay results (11,36). Of note, S/CO values of less than 10 by the ARC and BPX assays have frequently been associated with false-positive results (31,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 71%
“…HIV infection (8)(9)(10)(11). Negative results on standard HIV Ab tests are common among HIV-1-infected children who initiate ART at an early age (12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Obviously, it is strictly related to different phases (for example, during sampling), and it could be avoided following the prescribed procedures in the case of viral infection [ 34 ]. Moreover, as demonstrated in other viral infections such as HIV, another important problem is related to the use of antiretroviral therapy: indeed, the viral load could be insufficient to be detected, generating false negative results [ 35 ].…”
Section: Covid-19 Laboratory-based Molecular Testingmentioning
confidence: 99%
“…Among the 90 pieces of evidence that were identified through country survey and systematic review and that met the inclusion criteria, 65 (88%) 1,4,5,[7][8][9][10][11][12][13][14][15]20, focused on assay performance, algorithm performance, or methodological descriptions of incidence estimation.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Factors that can affect assay performance include natural variability in individual immune responses (in particular, elite control of HIV or natural viral suppression), variability in biomarker progression for different HIV-1 subtypes, the types of specimens collected and storage methods, advanced HIV disease, and treatment with antiretroviral therapy (ART) or use of pre-exposure prophylaxis (PrEP). [5][6][7][8][9][10] The effect of ART on increasing the FRR of recency assays appears to be more pronounced when a person receives treatment very early after initial infection; 11,12 which is complicated by rapid improvements in treatment coverage worldwide, as well as uptake of pre-exposure prophylaxis (PrEP). Other factors that may impact assay performance but are not yet well-characterised include sex, pregnancy status and the presence of co-morbidities.…”
Section: Introductionmentioning
confidence: 99%